Unique tau- and synuclein-dependent metabolic reprogramming in neurons distinct from normal aging. - Yadav, S.; Graham, A.; Al Hammood, F.; Garbark, C.; Vasudevan, D.; Pandey, U.; Asara, J.M.; Rajasundaram, D.; Parkhitko, A.A. (Aging Cell, 2024)
Neuronal cells are highly specialized cells and have a specific metabolic profile to support their function. It has been demonstrated that the metabolic profiles of different cells/tissues undergo significant reprogramming with advancing age, which has often been considered a contributing factor towards aging-related diseases including Alzheimer's (AD) and Parkinson's (PD) diseases. However, it is unclear if the metabolic changes associated with normal aging predispose neurons to disease conditions or a distinct set of metabolic alterations happen in neurons in AD or PD which might contribute to disease pathologies. To decipher the changes in neuronal metabolism with age, in AD, or in PD, we performed high-throughput steady-state metabolite profiling on heads in wildtype Drosophila and in Drosophila models relevant to AD and PD. Intriguingly, we found that the spectrum of affected metabolic pathways is dramatically different between normal aging, Tau, or Synuclein overexpressing neurons. Genetic targeting of the purine and glutamate metabolism pathways, which were dysregulated in both old age and disease conditions partially rescued the neurodegenerative phenotype associated with the overexpression of wildtype and mutant tau. Our findings support a "two-hit model" to explain the pathological manifestations associated with AD where both aging- and Tau/Synuclein- driven metabolic reprogramming events cooperate with each other, and targeting both could be a potent therapeutic strategy.